Patient Awareness of Additive Manufacturing in Dentistry – A Survey - Shopova, Dobromira; Bakova, Desislava; Semerdjieva, Maria; Yaneva, Antonia (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: Additive manufacturing or 3D printing technology creates the object layer by layer. Its development in dentistry has been particularly rapid over the last ten years and covers more and more dental fields. The aim of this article is to demonstrate the patient’s awareness of additive manufacturing and their opinion about the price and application of 3D printed products in dentistry. Materials and methods: The survey was distributed to a total of 111 patients, of whom 49.5% were men and 50.5% were women. The majority of respondents have higher education. Their age varies from 34 to 76. Students do not participate in the survey. More than half of the respondents (55.5%) are retired. Results and conclusion: Patients are mainly informed by dentists but consider themselves insufficiently informed. 3D printed versions are rarely offered, especially for temporary constructions. Patients rate the price as too high, but would not give up treatment only for that reason. They are hesitant in their choice for treatment with a classic or 3D printed technique.